Kingdom. 2 - Hara, Yasuhisa, 1975- (VIZ Media, LLC, 2026)
Xin is a war orphan in a poor village in the kingdom of Qin. He has big dreams of becoming the Greatest General Under the Heavens, and when his best friend's life is cut short by political machinations, Xin finds himself on a quest to do what no one has ever done before--unify China. After safely meeting with Lord Changwen and soldiers still loyal to the rightful king, Ying Zheng and his company must decide on the next steps to reclaiming his throne. Meanwhile, Xin and Diao are completely out of their element around these soldiers and advisors, many of whom are confused and shocked by their presence. But seeing Diao gives Lord Changwen an idea on where to start their quest--meet with the Mountain King. But it won't be easy, as their treaties lapsed hundreds of years prior, and outsiders are not welcome.